Maternal adjustment of offspring provisioning and the consequences for dispersal. Issue 10 (1st October 2015) - Larios, Eugenio; Venable, D. Lawrence
Abstract : Phenotypic plasticity in seed provisioning is a widespread phenomenon in plant populations that is often manifested as environmentally induced maternal effects. Environmental maternal effects can be beneficial if they influence population dynamic functions of seeds in a way that increases fitness, such as escaping from crowding. Using the winter annual plant, Dithyrea californica, we studied the response of seed provisioning to the maternal competitive environment and the associated seed dispersal consequences. We measured the average size of seeds produced by plants experiencing different competitive environments in order to test the hypothesis that mother plants respond to crowding by providing fewer resources to each offspring. We also hypothesized that smaller seeds produced by crowded mothers would benefit from greater dispersal away from their high‐density natal habitat. We marked seeds with fluorescent paint while still attached to the mother plant, recorded seed diameter, and followed them for nine months after dispersal, recording the distance they moved from the mother plant. Plants that experienced more competition produced smaller seeds that dispersed farther from their mother plant. Larger seed diameter was previously shown to be associated with greater competitive ability in D. californica . Thus the production of smaller seeds in more competitive environments implies a possible trade‐off between competitive ability and dispersal arising from an environmentally driven aspect of phenotype. Fitness consequences of this trade‐off in the context of the year‐to‐year variation in rainfall and density are uncertain.